ABBA gold greatest hits. - ABBA (Musical group) ([New York] : Polar, 1999)
The first album produced for CD by the '70s supergroup features 19 songs. The Gold collection is the simplest and most clear-cut collection of the group's best material.
Dancing queen -- Knowing me, knowing you -- Take a chance on me -- Mamma mia -- Lay all your love on me -- Super trouper -- I have a dream -- The winner takes it all -- Money, money, money -- S.O.S -- Chiquitita -- Fernando -- Voulez vous -- Gimme! Gimme! Gimme! (A man after midnight) -- Does your mother know -- One of us -- The name of the game -- Thank you for the music -- Waterloo.
Compilation of recordings previously released, p1974- p1983.
Compact disc.
Program notes inserted in container.
ABBA: Bj?n Ulvaeus, Benny Andersson, Agnetha Fl~tskog, Anni -Frid (Frida) Lyngstad.
Keywords: Popular music -- 1971-1980.; Popular music -- 1981-1990.; Rock music -- 1971-1980.; Rock music -- 1981-1990.